Meta-analytic evidence of low convergence between implicit and explicit measures of the needs for achievement, affiliation, and power - Köllner, Martin G.; Schultheiss, Oliver C. (Frontiers in Psychology, 2014)
The correlation between implicit and explicit motive measures and potential moderators of this relationship were examined meta-analytically, using Hunter and Schmidt’s (2004) approach. Studies from a comprehensive search in PsycINFO, data sets of our research group, a literature list compiled by an expert, and the results of a request for grey literature were examined for relevance and coded. Analyses were based on 49 papers, 56 independent samples, 6151 subjects, and 167 correlations. The correlations (ρ) between implicit and explicit measures were 0.130 (CI: 0.077 - 0.183) for the overall relationship, 0.116 (CI: 0.050 - 0.182) for affiliation, 0.139 (CI: 0.080 - 0.198) for achievement, and 0.038 (CI: -0.055 - 0.131) for power. Participant age did not moderate the size of these relationships. However, a greater proportion of males in the samples and an earlier publication year were associated with larger effect sizes.